To divide fractions, we multiply the first fraction by the reciprocal of the second fraction.
The reciprocal of -3/2 is -2/3.
So, −5/6 ÷ (−3/2) is equivalent to −5/6 × (−2/3).
When multiplying fractions, we multiply the numerators together and the denominators together.
(-5/6) × (-2/3) = (5 × 2) / (6 × 3)
= 10/18
Simplifying the fraction gives us:
10/18 = 5/9
−5/6÷(−3/2)
3 answers
−4 2/3÷3 1/5
To divide mixed numbers, we convert them to improper fractions and then proceed with the division.
Let's first convert the mixed numbers to improper fractions.
-4 2/3 = -4 + 2/3 = (-4 * 3 + 2) / 3 = (-12 + 2) / 3 = -10/3
3 1/5 = 3 + 1/5 = (3 * 5 + 1) / 5 = (15 + 1) / 5 = 16/5
Now, we can divide -10/3 by 16/5.
(-10/3) ÷ (16/5) = (-10/3) * (5/16)
When multiplying fractions, we multiply the numerators together and the denominators together.
(-10/3) * (5/16) = (-10 * 5) / (3 * 16) = -50/48
Now, we can simplify the fraction.
-50/48 = -25/24
So, -4 2/3 ÷ 3 1/5 is equal to -25/24.
Let's first convert the mixed numbers to improper fractions.
-4 2/3 = -4 + 2/3 = (-4 * 3 + 2) / 3 = (-12 + 2) / 3 = -10/3
3 1/5 = 3 + 1/5 = (3 * 5 + 1) / 5 = (15 + 1) / 5 = 16/5
Now, we can divide -10/3 by 16/5.
(-10/3) ÷ (16/5) = (-10/3) * (5/16)
When multiplying fractions, we multiply the numerators together and the denominators together.
(-10/3) * (5/16) = (-10 * 5) / (3 * 16) = -50/48
Now, we can simplify the fraction.
-50/48 = -25/24
So, -4 2/3 ÷ 3 1/5 is equal to -25/24.